Liberal Peace Intervention in the Central African Republic: Limitations and Reworking a "Hybrid" Order. Issue 1 (2nd January 2017) - Maiangwa, Benjamin; Suleiman, Muhammad Dan
Abstract: This article uses Roger Mac Ginty's four-part model of hybridity as a conceptual paradigm to reconsider the relative failure of the liberal peace intervention as a model of building peace in the Central African Republic. The article argues that the limited success of the liberal peace intervention in the Central African Republic is due to its strict adherence to internationalist, top-down, and exclusionary approaches. This, the article argues, eventually obscures local agency, reduces local stakeholder actors to irrelevance, and derails any prospect of ensuring cross-community reconciliation programs. Thus, we conclude that a more inclusive approach, involving participatory, locally engineered, and hybridized LPI—which enforces and brings in the utility of local actors, resources and practices—would be a more effective way of sidestepping the defective trappings of fundamentally "foreign" interventionist paradigms in the Central African Republic.